2016
DOI: 10.7883/yoken.jjid.2015.421
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Inhibition of Cholera Toxin Production in <i>Vibrio cholerae</i> by Methanol Extract of Sweet Fennel Seeds and Its Components

Abstract: SUMMARY: A newly emerged Vibrio cholerae O1 El Tor variant strain with multidrug resistance is considered a threat to public health. Recent strategies to suppress virulence factors production instead of bacterial growth may lead to less selective pressure for the emergence of resistant strains. The use of spices and their active constituents as the inhibitory agents against cholera toxin (CT) production in V. cholerae may be an alternative approach to treat cholera. In this study, we examined the potential of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…It has been shown that essential oils obtained from the fennel leaves are characterized by a high anethole concentration and antimicrobial activity against Gram-positive bacteria ( Senatore et al, 2013 ). Furthermore, another study reported that the Gram-negative food-borne pathogen, Vibrio cholerae , was killed by methanol-extracted sweet fennel seeds by inhibition of cholera toxin production ( Chatterjee et al, 2016 ). However, the antimicrobial activity of fennel toward oral bacteria has not been systematically studied and mechanisms by which fennel contribute to antimicrobial activity remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that essential oils obtained from the fennel leaves are characterized by a high anethole concentration and antimicrobial activity against Gram-positive bacteria ( Senatore et al, 2013 ). Furthermore, another study reported that the Gram-negative food-borne pathogen, Vibrio cholerae , was killed by methanol-extracted sweet fennel seeds by inhibition of cholera toxin production ( Chatterjee et al, 2016 ). However, the antimicrobial activity of fennel toward oral bacteria has not been systematically studied and mechanisms by which fennel contribute to antimicrobial activity remain unknown.…”
Section: Introductionmentioning
confidence: 99%